Nitrogen Fertilisation Increases Specific Root Respiration in Ectomycorrhizal but Not in Arbuscular Mycorrhizal Plants: A Meta-Analysis - Bicharanloo, Bahareh; Cavagnaro, Timothy R.; Keitel, Claudia; Dijkstra, Feike A. (Frontiers in Plant Science, 2021)
Plants spend a high proportion of their photosynthetically fixed carbon (C) belowground to support mycorrhizal associations in return for nutrients, but this C expenditure may decrease with increased soil nutrient availability. Here we assessed how nitrogen (N) fertiliser effects on specific root respiration varied among mycorrhizal type. We conducted a multi-level meta-analysis across 1600 observations from 32 publications. Specific root respiration increased in ectomycorrhizal (ECM) plants with more than 100 kg N ha-1 applied, did not change in arbuscular mycorrhizal (AM) and non-mycorrhizal plants, but increased in plants with dual mycorrhizal association in response to N fertilisation. Our results suggest that high N availability (>100 kg N ha-1) could disadvantage growth of ECM plants because of increased C costs associated with maintaining higher root N concentrations, while the insensitivity in specific root respiration by AM plants to N fertilisation may be because AM fungi are more important for phosphorus uptake.